Implementasi Komunikasi Profetik oleh Ta’mir untuk Meningkatkan Partisipasi Jamaah: Studi Kasus Masjid Nurul Azhar, Sumbermalang - M. Khairul Basyar; Zakiyah Romadlany (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines the implementation of prophetic communication by the administrators of Nurul Azhar Mosque in Sumbermalang to increase congregational participation. The study is motivated by the tendency of mosque activities to depend not only on program availability but also on the quality of communication between mosque administrators and congregants. Using a qualitative case study design, data were collected through semi-structured interviews, participant observation, and documentation. The informants consisted of one mosque administrator and six congregants selected purposively based on their involvement in mosque activities. Data were analyzed interactively through data condensation, data display, and conclusion drawing, while validity was strengthened through source triangulation, technique triangulation, and member checking. The findings show that prophetic communication is implemented through three interrelated dimensions. Humanization appears in empathetic, dialogical, and personal communication that builds emotional closeness and a sense of belonging. Liberation is reflected in the involvement of congregants in planning, decision-making, and program implementation, thereby transforming them from passive participants into active subjects. Transcendence is embodied in the strengthening of religious values that connect congregational participation with worship and devotion to Allah SWT. The study contributes to the development of prophetic communication studies by showing that humanization, liberation, and transcendence operate as a sequential and mutually reinforcing communication mechanism in mosque management. Prophetic communication, therefore, can be used as a practical strategy to strengthen sustainable social and spiritual engagement in mosque-based community development.